2023
DOI: 10.1111/jfpe.14304
|View full text |Cite
|
Sign up to set email alerts
|

Detection of starch in minced chicken meat based on hyperspectral imaging technique and transfer learning

Abstract: In order to the quickly and nondestructively detect whether starch is adulterated in minced chicken meat, a novel method combining hyperspectral imaging (HSI) technique with transfer learning was proposed in this study. First of all, hyperspectral images of minced chicken meat with different mass fractions of starch were collected and spectral information of the samples in the range of 400.89-1000.19 nm was extracted. Then, the hyperspectral data was preprocessed via continuous wavelet transform (CWT), which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The results of this investigation revealed a substantial decrease (P< 0.05) in the moisture content of all treated soybean samples, with roasting at 230 °C for 30 minutes yielding the lowest value of 2.18% [13]. Moreover, the e-nose has an ability to identify 11 volatile chemicals in Korean soybean, while the e-tongue assesses the intensity of 5 basic tastes [42]. Through the used of the principal component analysis, the contribution rates of the first and second principal components detected by electronic nose and tongue for minced chicken meat adulterated with soy protein were 99.2% and 0.6%, respectively, and the total contribution rate was 99.8% leading to the result that the combination of electronic nose and electronic tongue sensors has the potential to distinguish and predict soy protein-based or starch-based adulteration in minced chicken meat, and it has also been demonstrated to be a useful identification method for meat contamination detection with high efficiency and accuracy [43].…”
Section: Introductionmentioning
confidence: 76%
“…The results of this investigation revealed a substantial decrease (P< 0.05) in the moisture content of all treated soybean samples, with roasting at 230 °C for 30 minutes yielding the lowest value of 2.18% [13]. Moreover, the e-nose has an ability to identify 11 volatile chemicals in Korean soybean, while the e-tongue assesses the intensity of 5 basic tastes [42]. Through the used of the principal component analysis, the contribution rates of the first and second principal components detected by electronic nose and tongue for minced chicken meat adulterated with soy protein were 99.2% and 0.6%, respectively, and the total contribution rate was 99.8% leading to the result that the combination of electronic nose and electronic tongue sensors has the potential to distinguish and predict soy protein-based or starch-based adulteration in minced chicken meat, and it has also been demonstrated to be a useful identification method for meat contamination detection with high efficiency and accuracy [43].…”
Section: Introductionmentioning
confidence: 76%
“…Moreover, the e-nose has an ability to identify 11 volatile chemicals in Korean soybean, while the e-tongue assesses the intensity of 5 basic tastes [42]. Through the used of the principal component analysis, the contribution rates of the first and second principal components detected by electronic nose and tongue for minced chicken meat adulterated with soy protein were 99.2% and 0.6%, respectively, and the total contribution rate was 99.8% leading to the result that the combination of electronic nose and electronic tongue sensors has the potential to distinguish and predict soy protein-based or starch-based adulteration in minced chicken meat, and it has also been demonstrated to be a useful identification method for meat contamination detection with high efficiency and accuracy [43]. Hence, this device can be utilized in breeding as a fast screening tool programs, in the selection of soybean mutants/varieties with varying volatile profiles, as well as in the mapping of the QTLs and loci responsible for these features.…”
Section: A Backgroundmentioning
confidence: 99%
“…The findings confirm that integrating LRCNN with the e-nose effectively identifies gas information associated with soybeans from various growing areas, presenting a promising new method for soybean quality traceability. Another study where the electronic nose is coupled with an effective deep learning method is a study where they introduce the adaptive convolutional kernel channel attention network (AKCA-Net) coupled with an electronic nose (enose) to establish traceability in soybean quality [43]. The e-nose system is initially employed to gather gas information from soybeans of various origins.…”
Section: E Impact Of Electronic Nose On Soybean Quality Assessmentmentioning
confidence: 99%
“…Currently, the detection of meat product freshness typically involves the use of traditional physical and chemical methods (Elisseeva et al, 2020; Li et al, 2017; Li & Wang, 2021), odor sensor technology (Li et al, 2022; Liu & Fang, 2019), electronic nose technology (Huang & Gu, 2022; Li et al, 2023; Liu et al, 2022; Wakhid et al, 2022), near‐infrared (NIR) technology (He et al, 2019; Lam et al, 2020; Zhang et al, 2022), hyperspectral imaging (HSI) technology (Shi et al, 2022; Yang et al, 2023; Zhuang et al, 2022), and other techniques. In terms of meat quality detection, Dong et al (2023) employed hyperspectral technology to establish a regression model based on full‐spectrum and characteristic wavelengths, and found that the partial least squares regression model exhibited the best predictive performance.…”
Section: Introductionmentioning
confidence: 99%